Teacher subject matter knowledge for the meaningful transition from arithmetic to algebra - Pınar Yıldız; İ. Elif Yetkin Özdemir (Journal of Pedagogical Research, 2021)
Teacher knowledge is particularly important in middle school mathematics to enhance the meaningful transition from arithmetic to algebra. Developing a solid understanding of algebra requires teachers to unpack the meaning underlying the basic concepts, make clear and explicit distinctions among concepts, and facilitate students to connect these concepts with their prior knowledge and understandings in arithmetic. This study focused on the content knowledge (i.e., decompose, trim, and bridge) of three middle school mathematics teachers in practice during the introduction of basic algebra concepts (i.e., variable, algebraic expression, equality and equations). Case study was used as research design in this research. Individual interviews and observations regarding the instructions were used to gather data. Results showed that the participating teachers' conceptions regarding the variable, algebraic expression and equation were rather narrow and it resulted in several constraints when unpacking their meaning in the classroom. While bridging was a commonly observed instructional practice among the participating teachers, the quality of bridging, did not always provide opportunities for a meaningful transition. Trimming, on the other hand, was not observed as a common teaching practice.